Majas pada Lirik Lagu Nadin Amizah dalam Album Selamat Ulang Tahun - Ilfa Shofia Noer; Harjito Harjito; Zainal Arifin (Universitas PGRI Semarang, 2023)
The purpose of this study is to describe what figure of speech is contained in the lyrics of the song Nadin Amizah in the â€œHappy Birthday Albumâ€. The research method uses descriptive qualitative with stylistic studies. The data analysis method used the content analysis method with stages (1) determining all available data, (2) description or orientation, (3) reduction phase and (4) selection phase. The research data was taken from Nadin Amizah's official you tube on his first album entitled